Persepsi Generasi Z Terhadap Toleransi Beragama di Media Sosial - Manuain, Leryani Mince Maria; Moru, Osian Orjumi; Renda, Trijuliani; Pellondou, Andri Oktovianus; Naitboho, Junita (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
This research regards a perception of Generation z in Kupang to tolerance religion on Social Media and influencing factors perception of Generation z Kupang City To Tolerance Religious on Social Media. Study this using method study combination (mixed methods). In a study, this researcher collects, analyzes data, integrates findings, and describes a conclusion with combined method study qualitative and quantitative. The average score perception generation z against tolerance of religion on social media seen from indicators of Fairness, empathy and reasonableness is at one category enough, that is by 64.1 %. In line with that, the results of qualitative data show that the average generation z is tolerant of differences that exist, but attitude intolerant sometimes appears influenced by internal factors, namely: Experiencing life with different experiencing life together Becomes a factor of mutual understanding. Understanding to teachings of religion Becomes a factor that shapes positive perceptions _ and is hostile towards people, religious others, and with live values and spirit nationality, generation z tends to own a positive perception _ about tolerance of religion. In using social media, they put forward identity and nationality. Different people's confidence with they responded and greeted by cheerful. Referring to on conclusion above, the Institution or institution education needs to develop a curriculum that answers the need for public tolerance of religion and also needs _ the existence of specialization about attitude tolerant in the use of social media by wise